BMI and related risk factors among U.S. Marshallese with diabetes and their families. Issue 8 (17th November 2021) - Wang, Monica L.; McElfish, Pearl A.; Long, Christopher R.; Lee, Morgan S.; Bursac, Zoran; Kozak, Andrea T.; Ko, Linda K.; Kulik, Noel; Kim Yeary, Karen Hye-cheon
ABSTRACT: Objective: Examine cross-sectional associations between body mass index (BMI) and related health behaviors, barriers and facilitators to health care, and perceived health status among a sample of U.S. Marshallese adults with Type 2 diabetes and evaluate associations of interest between participants and their family members. Design: Cross-sectional baseline data were analyzed from participants in a diabetes self-management education intervention trial. Setting: Data collection took place in home or community settings through a community-academic partnership in Arkansas. Participants: Study participants consisted of U.S. Marshallese adults with Type 2 diabetes ( N  = 221) and their family members ( N  = 211) recruited through community settings. Intervention(s): N/A. Main Outcome Measure(s): Participants' height and weight were measured using standard protocols to calculate BMI (kg/m 2 ). Diet, physical activity, health care access, financial strain related to health care, perceived health status, and health care satisfaction were measured using self-report surveys. Results: Participants' mean BMI was 31.0 (95% CI: 30.2–31.7), with over half of study participants and their family members' BMI falling in the obese category. Participants' BMI was positively associated with spreading health care bill payments over time ( β  = 1.75 (SE = 0.87); p  = 0.045). Positive associations between participants and their family members were observed for self-reported health status conditions, health care coverage, health care utilization, and health care satisfaction. Conclusion: Study findings highlight the high prevalence of obesity and related risk factors among U.S. Marshallese adults with Type 2 diabetes and emphasize the need for intervention strategies that build upon cultural strengths and target community, policy, systems, and environmental changes to address obesity and chronic disease in this marginalized community.